2016
DOI: 10.1183/13993003.00412-2016
|View full text |Cite
|
Sign up to set email alerts
|

Lower lung function associates with cessation of menstruation: UK Biobank data

Abstract: Little is known about the effect of cessation of menstruation on lung function. The aims of the study were to examine the association of lung function with natural and surgical cessation of menstruation, and assess whether lower lung function is associated with earlier age at cessation of menstruation.The study was performed in 141 076 women from the UK Biobank, who had provided acceptable and reproducible spirometry measurements and information on menstrual status. The associations of lung function (forced vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
1
28
1
1
Order By: Relevance
“…A recent systematic review supports an association of menopause with lower forced expiratory volume in 1 s (FEV1) and lower forced vital capacity (FVC) [4]. A large study in the UK Biobank (UKB) showed that women with an earlier age at menopause had lower FEV1 and FVC, and a higher risk of spirometric restriction, while no association was found with airflow obstruction [5]. These observational studies may suffer from residual confounding even when the analyses are adjusted for known confounders, including anthropometric, lifestyle, socio-economic and reproductive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review supports an association of menopause with lower forced expiratory volume in 1 s (FEV1) and lower forced vital capacity (FVC) [4]. A large study in the UK Biobank (UKB) showed that women with an earlier age at menopause had lower FEV1 and FVC, and a higher risk of spirometric restriction, while no association was found with airflow obstruction [5]. These observational studies may suffer from residual confounding even when the analyses are adjusted for known confounders, including anthropometric, lifestyle, socio-economic and reproductive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in understanding gender-related risk factors for lung function impairment, particularly in relation to hormonal influences and sexual development. Substantial evidence shows that lung function is influenced by sex hormones in women [ 14 ] for whom low lung function has been associated with irregular menstruation, menopausal transition, and both natural and surgical menopause, with report of improvement in lung function in postmenopausal women receiving hormone replacement therapy [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amaral et al previously reported decreased lung function in postmenopausal women in UK Biobank 16. We repeat these analyses for completeness alongside analyses of other female reproductive health indicators.…”
Section: Methodsmentioning
confidence: 92%
“…A recent systematic review, which included studies from UK Biobank,16 reported that postmenopausal status was associated with reduced FEV 1 and FVC but not FEV 1 /FVC 18. Current HRT use has been associated with both higher14 and lower15 lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation